(untitled) (World Science, 2019)
The purpose of the work is the quantitative assessment of the impact of climate change on the runoff of the rivers of Georgia and, consequently, on their hydropower potential. To this end, the sections of 19 river basins located in six regions of Georgia, where natural runoff is maintained, have been reviewed – it is not regulated. The results of the study confirm the change of the water content of the selected rivers and hence their hydro- energy potential, which is related to the climate transformation process.